Strategies to enhance production of a recombinant lignin peroxidase in Pichia pastoris - Biko, Odwa Dinilesizwe Vuyani (Stellenbosch ; Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.